Structural brain changes in hyperthyroid Graves’ disease: protocol for an ongoing longitudinal, case-controlled study in Göteborg, Sweden—the CogThy project - Rolf A Heckemann; Mats Olof Holmberg; Helge Malmgren; Peter Berglund; Lina Bunketorp-Käll; Birgitta Johansson; Niklas Klasson; Erik Olsson; Simon Skau; Helena Nystrom Filipsson (BMJ Open)
Introduction Cognitive impairment and reduced well-being are common manifestations of Graves’ disease (GD). These symptoms are not only prevalent during the active phase of the disease but also often prevail for a long time after hyperthyroidism is considered cured. The pathogenic mechanisms involved in these brain-derived symptoms are currently unknown. The overall aim of the CogThy study is to identify the mechanism behind cognitive impairment to be able to recognise GD patients at risk.Methods and analysis The study is a longitudinal, single-centre, case-controlled study conducted in Göteborg, Sweden on premenopausal women with newly diagnosed GD. The subjects are examined: at referral, at inclusion and then every 3.25 months until 15 months. Examinations include: laboratory measurements; eye evaluation; neuropsychiatric and neuropsychological testing; structural MRI of the whole brain, orbits and medial temporal lobe structures; functional near-infrared spectroscopy of the cerebral prefrontal cortex and self-assessed quality of life questionnaires. The primary outcome measure is the change in medial temporal lobe structure volume. Secondary outcome measures include neuropsychological, neuropsychiatric, hormonal and autoantibody variables. The study opened for inclusion in September 2012 and close for inclusion in October 2019. It will provide novel information on the effect of GD on medial temporal lobe structures and cerebral cortex functionality as well as whether these changes are associated with cognitive and affective impairment, hormonal levels and/or autoantibody levels. It should lead to a broader understanding of the underlying pathogenesis and future treatment perspectives.Ethics and dissemination The study has been reviewed and approved by the Regional Ethical Review Board in Göteborg, Sweden. The results will be actively disseminated through peer-reviewed journals, national and international conference presentations and among patient organisations after an appropriate embargo time.Trial registration number 44321 at the public project database for research and development in Västra Götaland County, Sweden (https://www.researchweb.org/is/vgr/project/44321).